PROBLEMS OF DEVELOPMENT OF THE ELECTRIC POWER INDUSTRY BASED ON IOT TECHNOLOGY - Kalimoldayev, М.Н.; Abdildaeva, А.А.; Shermantaeva, Ж.У.; Waldemar, Вoйцик (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The development and spread of digital and intelligent (IoT) technologies, their radical penetration into all sectors of the economy and society is gaining momentum, changing traditional business models, traditional industry structures and schemes of world markets. The scale of the changes is so great that it is safe to say that this is another technological revolution in which digitalization is almost synonymous with competitiveness. Despite the fact that the idea of the "Internet of Things" appeared about 20 years ago, the active development of technologies began only in recent years. The relevance of this direction is constantly growing. A smart environment is impossible without the interaction of its objects, and it is the concept of the Internet of Things (IoT) that takes this interaction to a new level. The Internet of Things allows you to quickly obtain factual information, quickly analyze it, and, accordingly, make informed decisions and measures. The paper explains the terms "IoT technologies in the energy sector", which define the unique content of the processes behind them. A conceptual vision of the development of the electric power industry based on the principles of IoT technologies and a development scenario are presented. The Internet of Things (IoT) is beginning to define the future of many industries and emerging markets. One of the IoT target markets is energy systems. IoT is the production, transmission and processing of information, so everything that is part of the system, including software and hardware, should be considered as a whole. This article presents the current state of IoT-based energy systems to review the latest activities for each IoT component in energy systems. Problems in this subject area are discussed, and then some solutions are presented.